Adaptive Capability of Farmer Group in Management of Lowland Rice Variety for Self-Reliance Production for Fai Kaew Community Enterprise in Fai Kaew Sub-District, Phupieng District, Nan Province - Sakitram, Phimonphan (Journal of Community Development Research (Humanities and Social Sciences), 2020)
RD 6 rice variety is a well-known glutinous jasmine rice and widespread adoption variety in Northern Thailand and Nan province. This variety is threatened by rice blast disease, which is a serious rice disease in the area. Farmers are losing their yields. To solve this problem, a group of farmers in Nan province integrated scientific knowledge and local knowledge in a participatory rice varieties selection approach to achieve new rice varieties. This study applied the mixed methods. It relied on both quantitative and qualitative data encompassing secondary data gathering, field observation, in-depth interviews with farmers, non-government organization staffs, government organizations and related stakeholders involved in the operation of managing lowland rice variety for self-reliant production at Fai Kaew (FK) community enterprise, Nan Province, Thailand. The study revealed that the probability problem solving is the management of rice variety that had been implemented continuously. FK farmers’ capability to adapt can occur along the way in the cycle of the learning process. They collaborated with rice researchers and non-government organization to select new rice varieties by integrating their local knowledge with scientific knowledge. Consequently, FK farmers can develop new rice varieties that are resistant to rice blast disease, namely Thayasirin and Nan 59. The main discussion is that the adaptive capacity that farmers as key actors can be ready to adapt and develop new solutions or interventions whenever new problems/constraints affect them in rice production and livelihood. Farmers deal with problems by integrating data and knowledge and collaborating with other stakeholders to select rice varieties that are suitable and respond to the farm ecological system, productivity and profitability. Thus, the management of farmers’ rice varieties is a dynamic and continuous process. The adaptive capability is one of components of self-reliance of management of farmers’ rice varieties. Keywords: Adaptive Capability, Self-Reliance Production, Sustainable Agriculture, Rice Varieties